Strategi Pembelajaran Berbasis STEAM Dengan Bermain Loose Parts Untuk Pencapaian Keterampilan 4c Pada Anak Usia 4-5 Tahun - Prameswari, Titania; Anik Lestariningrum (Universitas Nusantara PGRI Kediri, 2020)
Learning problems in producing students who have 4c competence (creativity, communication, collaboration, critical thinking) are still very limited, especially in PAUD. The problem can be seen from the achievements of children's development were limited creativity when teaching learning process occurs, children have low communication skills and express opinions from the results of groups or collaborations. This is due to the role of the teacher is still dominant in teaching learning process and teacher limits the children's creativity by providing less varied of learning media because it only uses student worksheets that are available at school. STEAM-based learning (Science, Technology, Engineering, Art, Mathematic) with loose parts media was chosen because it is in line with 21st century education where critical thinking skills, creative, collaborative and communicative are honed by playing. Based on the results of observation showed that learning activities implemented by teacher in Group A Pertiwi 2 Bodor Kindergarten did not lead to 21st century learning yet so that learning activities were monotonous and the teacher was not be able to direct students to master the 4c ​​skills. From these problems, the teacher applied STEAM-based learning by using Loose Parts media. The research method used descriptive qualitative with 13 subjects of Group A aged 4-5 years old at TK Pertiwi 2 Bodor. Data collection was done by observation and documentation techniques, then it was analyzed qualitatively that is analyzing the child's developmental achievements objectively. The results showed that STEAM-based learning using loose parts media effectively was increased the ability of 4c children aged 4-5 years, so it is recommended that this learning can be implemented continuously to see the students’ achievement in other aspects.